Imago Dei Berhadapan dengan Pernikahan Sesama Jenis - Marcellino, Wiliam (Felicitas, 2025)
The phenomenon of same-sex marriage has elicited various responses—socially, culturally, and theologically. This paper is motivated by the need to understand how the concept of imago Dei, or the human being as the image and likeness of God, confronts the reality of same-sex marriage within the framework of Catholic teaching. The purpose of this writing is to critically examine the Church’s perspective on human dignity, particularly concerning individuals who identify as LGBTQ+, and to explore the theological stance on same-sex unions. The central question raised is how the imago Dei is understood in relation to human identity and how this notion interacts with the reality of same-sex marriage. The discussion covers theological insights from the Book of Genesis, the thoughts of the Church Fathers, and official Church documents such as Fiducia Supplicans. The author concludes that although humans inherently bear the image of God, the effects of original sin and concupiscence have led to misuses of free will. Same-sex unions do not reflect the original purpose of human creation as intended by God. Nevertheless, those involved in such relationships still retain their dignity as God's creation. The Church is thus called to accompany and guide them toward the truth revealed in Christ.